The effect of cognitive aid design on the perceived usability of critical event cognitive aids. Issue 3 (25th November 2019) - Clebone, Anna; Burian, Barbara K.; Tung, Avery
Abstract : Background: Critical events require that clinicians process information and make decisions quickly. To reduce mental workload during such events, cognitive aids have been developed. We have previously observed that designing such aids to facilitate discrete information transfer decreased time to information finding. However, whether clinicians perceive aids designed for discrete information transfer as more usable than step‐by‐step designs remains unclear. We hypothesized that experimental cognitive aids designed for discrete information transfer would be judged more usable than step‐by‐step Linear aids. Methods: Volunteer clinicians were asked to use cognitive aids during low fidelity simulation scenarios. Experimental cognitive aids featuring color‐coded, labeled, and consistently located content clusters were compared with aids formatted in a traditional step‐by‐step fashion. We then performed a quantitative assessment of perceived usability and conducted structured knowledge elicitation interviews. Results: Clinicians rated the two experimental cognitive aids as more usable than the Linear aid. On a 0‐100 scale the median (IQR) rating was 25(18, 23) for the Linear aid and 89(80, 95) and 81(65, 90) for the two experimental designs, respectively, with a higher number indicating greater ease of use ( P < .01 for each). Narrative responses suggested specific features that improved usability and a thematic analysis identified six major themes driving preference for cognitive aid use. Conclusion: During simulated critical events, cognitive aids designed for discrete information transfer were considered more usable than step by step Linear aids. Specific themes governing usability were identified during mixed methods analysis. Further work is needed to optimize cognitive aid use among anesthesia clinicians.